Theoretical and applied research on hydraulic slit-fracture joint roof control and pressure relief of hard roof in goaf roadway - Yongjiang ZHANG; Fei JI; Tongbin ZHAO; Ke YANG; Wenbin WU; Wangang JIANG (Meitan xuebao)
Lateral cantilever beam structure is easy to be formed after extracting coal from working face under hard top plate, resulting in the superposition of the dynamic pressure of mining and the high hydrostatic pressure caused by the lateral overhanging rock layer and transferring to the mine roadway through the key layer, which causes the destabilization and large deformation of the peripheral rock structure of the roadway in the neighboring working face. In order to improve the rock structure of roof plate, adjust the breaking and transporting law of hard rock layer, and then control the strong mine pressure in the adjacent roadway, this paper analyzes the distribution law of mine pressure in the mine roadway, adopts numerical simulation means to study the distribution of the support pressure in the adjacent roadway under the hard roof plate, investigates the mechanism of the peripheral rock structure transferring loads under the conditions of different roof-cutting parameters, and puts forward a joint method of cutting top plate to remove the pressure by the abrasive jet ultra-high pressure hydraulic cutting - hydraulic fracturing. The method of roof cutting and pressure relief is proposed. The results of the study show that the mine pressure in the goaf roadway is the result of the coupling of dynamic and static loads, which is mainly manifested in the coupling of the high dynamic pressure caused by mining and the static load pressure of the lateral overhanging roof of the goaf roadway. The coupling effect is transmitted to the bottom plate by the surrounding rock in the limit equilibrium area on both sides of the roadway, and then produces a large range of plastic deformation in the bottom plate. Through the abrasive jet ultra-high-pressure hydraulic slitting technology, the slots are preset in the hard top plate, which can play a guiding role for the hydraulic fracturing cracks to drag and expand, and increase the influence range of hydraulic fracturing cracks by opening up the original cracks in the rock body, forming a continuous weak surface in a hard roof to weaken the stress transmission of the roof, and the depth of the slits is positively correlated with the slit pressure and the sand mixing ratio. The roof strata will interact with each other during the collapse process, and the changes in fracture angle and height will lead to changes in the sliding speed of the fractured rock mass and significant differences in the support force of the high-level rock strata. In the range of 66°～86°, the tensile stress on the rock layer at the top of the cut-off is increasing with the decrease of the top-cutting angle, and the rate of tensile stress increase is faster with the increase of the top-cutting height. When the range of the top-cutting height is 26～56 m, the fracture angle at which the tensile stress of the rock formation at the fracture point is higher than the ultimate tensile strength increases with the increase of the top-cutting height. Based on the above research, an industrial test was carried out at the 81403 working face of the Huayang mine. The on-site monitoring results with the loads of supporting structure and deformation of surrounding rock as the indexes show that the anchor cable stress of the roof plate of the roadway was reduced by 35%, the stress of the roadway wall was reduced by 44%, the amount of roadway top and bottom plate migration was reduced by 57%, and the migration amount of the roadway two walls was reduced by 42%, which has a good effect of pressure relief. The research results can provide a new technical means for controlling the ground pressure in the gob roadway under the condition of hard roof.